IMPLEMENTASI SISTEM E-TICKETING SEBAGAI UPAYA MEWUJUDKAN PENGELOLAAN PARIWISATA BERKELANJUTAN PADA KAWASAN CAGAR BUDAYA TAMAN NARMADA KABUPATEN LOMBOK BARAT - Eko Esti Santoso; Mariana, Mariana; Titin Windiasari; Lale Ajeng Khalifatun Wardani; Vegalyra Novantini Samodra (Yayasan Nusantara Hasana Berdikari, 2026)
Digital transformation has become one of the primary strategies for improving destination governance toward effective, transparent, and sustainable tourism management. One innovation increasingly adopted in tourism destinations is the implementation of an electronic ticketing (e-ticketing) system to replace conventional ticketing. The Narmada Cultural Heritage Site in West Lombok Regency is one of the major historical and cultural tourism destinations in West Nusa Tenggara Province, attracting a considerable number of domestic and international visitors. Prior to digital implementation, ticket management relied heavily on manual processes, resulting in limited real-time visitor data, inefficient reporting systems, and potential revenue leakage. This community service program aimed to strengthen the capacity of destination managers in implementing the Btix E-Ticketing system as a tool to support sustainable tourism governance. The implementation stages included field observation, needs assessment, preparation of implementation modules, socialization of the Btix application, operational simulation, operator mentoring, and monitoring and evaluation through observations and pre-test–post-test assessments. The results indicate that all operators were able to operate the Btix application independently. The implementation improved service efficiency, transaction transparency, real-time visitor monitoring, and automated revenue reporting. Furthermore, the e-ticketing system supports sustainable tourism principles by promoting digital administration, reducing paper consumption, and providing accurate visitor data for evidence-based destination management and decision-making.